Detection of P2Y14 protein in platelets and investigation of the role of P2Y14 in platelet function in comparison with the EP3 receptor - Dovlatova, Natalia; Wijeyeratne, Yanushi D.; Fox, Susan C.; Manolopoulos, Panagiotis; Johnson, Andrew J.; White, Ann E.; Latif, M. Liaque; Ralevic, Vera; Heptinstall, Stanley (Thrombosis and Haemostasis, 2008)
mRNA encoding the recently discovered P2Y14 receptor has been reported in platelets, but the presence of P2Y14 receptor protein and its functionality have not been studied. If P2Y14 is expressed along with P2Y1 and P2Y12 receptors it may have a role in haemostasis. It was the objective of this study to investigate the presence of the P2Y14 receptor in platelets and its role in platelet function. The effects of the agonist UDP-glucose were compared with those of sulprostone, a selective EP3 receptor agonist. Expression of P2Y14 receptor was investigated by immunoblotting and confocal microscopy. Platelet aggregation in platelet-rich plasma (PRP) and whole blood was measured using light absorbance and platelet counting. VASP phosphorylation was investigated using flow cytometry. Immunoblotting provided evidence for P2Y14 receptor protein and microscopy confirmed its presence on platelets. Despite this, UDP-glucose (up to 100 µM) did not induce platelet aggregation in either PRP or whole blood, and did not potentiate aggregation induced by other agonists. P2Y14 did not substitute for P2Y12 in experiments using the P2Y12 antagonist AR-C69931. No effect of UDP-glucose was seen on adenylate cyclase activity as measured by VASP phosphorylation. In contrast, sulprostone acting via the EP3 receptor promoted platelet aggregation with effects on adenylate cyclase activity. EP3 also partially substituted for P2Y12 receptor. We have demonstrated the presence of P2Y14 receptor protein in platelets, but no contribution of this receptor to several measures of platelet function has been observed. Further studies are necessary to determine whether the P2Y14 receptor in platelets has any functionality.
Keywords: P2Y14; KIAA0001; GPR105; UDP-glucose; platelet aggregation; EP3; sulprostone; P2Y12; P2Y1